Genospecies diversity of Lyme disease spirochetes in rodent reservoirs. - Richter, D (Centers for Disease Control and Prevention, 1999)
To determine whether particular Borrelia burgdorferi s.l. genospecies associate solely with rodent reservoir hosts, we compared the genospecies prevalence in questing nymphal Ixodes ticks with that in xenodiagnostic ticks that had fed as larvae on rodents captured in the same site. No genospecies was more prevalent in rodent-fed ticks than in questing ticks. The three main spirochete genospecies, therefore, share common rodent hosts.